Optimum Allocation of Microgrid and D-STATCOM in Radial Distribution System for Voltage Profile Enhancement Using Particle Swarm Optimization - Mezigebu Getinet Yenealem (International Journal of Photoenergy)
The integration of microgrid (MG) and distribution static synchronous compensator (D-STATCOM) controller in power system has become crucial for enhancing voltage profiles, improving system reliability, and minimizing power losses in radial distribution networks. This study presents an innovative approach for the optimal allocation of MG and D-STATCOM within a radial distribution system (RDS), aimed at significantly improving voltage profiles. Particle swarm optimization (PSO), a powerful and efficient metaheuristic algorithm, is utilized to determine the optimal sizing of MG and D-STATCOM controllers. The loss sensitivity factor (LSF) technique is employed to find the optimal position for D-STATCOM, and the voltage stability index (VSI) is used to determine the optimal location for MG. To validate the effectiveness of the PSO-based approach, simulations are conducted on a standard IEEE 30 bus RDS. The results indicate that the strategic placement of MGs and D-STATCOMs markedly enhances the voltage profile across the distribution network, leading to improved power quality and reduced technical losses.